Palmetto predators: monsters among us - Jones, Mark R. (History Press, 2007)
Introduction -- Richard Valenti: super Christian -- Lee Roy Martin: The Gaffney strangler -- Marc Evonitz: coward's way out -- Larry Gene Bell: God chose us -- Final justice - the life and crimes of Pee Wee Gaskins -- Richard Starrett: delusional denial -- James Neil Tucker: the $34 killer -- Sweet Eddie Fischer: one man epidemic -- The literate monster - Stephen Stanko -- Afterword -- Bibliography -- About the author